[3H]Ifenprodil binding in post-mortem brains of Cloninger type 1 and 2 alcoholics: A whole-hemisphere autoradiography study. Issue 3 (30th March 2015) - Kupila, Jukka; Kärkkäinen, Olli; Laukkanen, Virpi; Häkkinen, Merja; Kautiainen, Hannu; Tiihonen, Jari; Storvik, Markus
Abstract: The glutamate N -methyl-d -aspartate (NMDA) receptor NR2B subunits are sensitive to ethanol and are found in brain areas related to ethanol addiction, dependence, development of alcohol tolerance, and alcohol withdrawal syndrome. Previous studies indicate that early-onset Cloninger type 2 alcoholics have an intact, responsive, dopaminergic system in the nucleus accumbens (NAC), whereas type 1 alcoholics have dopaminergic defects. NR2B-containing NMDA receptors in the NAC are involved in both non-opioid and opioid receptor-mediated reward. Our aim was to evaluate the putative [ 3 H]ifenprodil binding alterations of NR2B receptors in limbic, hippocampal, and cortical brain areas of type 1 alcoholics ( n =8), type 2 alcoholics ( n =8), and control subjects ( n =10) by postmortem whole hemisphere autoradiography. We found significantly different binding levels among these three subject groups, and the main difference was localized in the decreased binding in type 2 alcoholics and controls in the nucleus accumbens. Although preliminary and from relatively small diagnostic groups, these results suggest pathological alterations in the NR2B-mediated reward system of type 2 alcoholics. Highlights: NR2B is a NMDA receptor subunit expressed highly in striatum. Chronic stress may decrease NR2B expression in nucleus accumbens. Alcohol consumption may affect NR2B expression and availability. The ifenprodil binding to NR2B polyamine sites was decreased in type 2 alcoholics. The decrease binding may indicate pathology exclusive to early-onset alcoholics.